Perempuan dalam Kesunyian: Mengenal Kehidupan dan Karya-karya Siti Rukiah Kertapati (1927-1996) - Peggy Nirwanjanti; Ratu Husmiati; Kurniawati Kurniawati (UIN Sunan Gunung Djati Bandung, 2023)
This article aims to introduce the figure of Siti Rukiah Kertapati as one of Indonesia's female writers. Through her works, we can see the turbulent revolution around the 1940s to 1960s from the perspective of the common person, especially that of a woman. The narrative of women in the revolution presented by Siti Rukiah Kertapati is not grandiose by making the main character a